Hedging an Efficient Portfolio against Expected Inflation Risk: An Applied Research in the Iraq Stock Exchange - Faisal Hasan Shoman, Hasanain; Muneer Isma'eel, Mustafa (Journal of Economics and Administrative Sciences, 2024)
This research aims to hedge the efficient portfolio of the investor against the expected inflation risk and to evaluate the extent of improvement in the quality of its performance. It has applied to an intentional sample of companies whose shares traded on the Iraq Stock Exchange, consisting of (37) companies, with (120) monthly observations for each company from 2012 to 2021. The simple ranking model of Elton et al. (1978) has been used to build the nominally efficient portfolio and the inflation-adjusted model of Chen and Moore (1985) to hedge a portfolio against expected inflation risk. The Sharpe, Treynor, Jensen, and M2 models have been used to evaluate the performance of portfolios. The research has reached several results. The most important of which is the presence of a big difference in the components of the efficient hedged portfolio compared to the nominal unhedged portfolio, in addition to the presence of a big difference in the amounts of investment weights between the two portfolios. The results of the analysis have also shown a significant improvement in the quality of the performance of the efficient portfolio that has hedged against the expected inflation risk compared to the unhedged nominal portfolio. The originality of the research and its scientific value lie in the fact that it is the first to adopt the inflation-adjusted model in hedging the efficient portfolios of investors against the inflation risk. In addition, it is the first knowledge contribution with empirical evidence about the efficient portfolio's hedging against that risk on the Iraq Stock Exchange.Paper type: Research Paper